PSVIII-20 Corn silage inoculated with Lactobacillus buchneri on performance and carcass characteristics of feedlot lambs. (7th December 2018) - Rossi, L; Silveira Rabelo, C; Dallantonia, E; Torrecilhas, J; da Silveira Feres, F; Reis, R
Abstract: The aim of this study was to evaluate the effect of the inclusion of inoculated corn silage on dry matter intake (DMI), feedlot days (FD), average daily gain (ADG), feed efficiency (FE), hot carcass weight (HCW) and hot carcass yield (HCY) of feedlot lambs. Twenty male lambs Dorper x Santa Inês (initial weight = 22 ± 2.9 kg) were randomly distributed in individual pens in two treatments: diet with inoculated silage as treatment group; diet with silage without inoculant as control group. The machine was regulated to cut the corn plant to 10 mm, the grains were processed on the machine, inoculated with Lactobacillus buchneri CNCM I-4323 at 1 x 10Lactobacillus buchneri does not affect the final products of the fermentation and the availability of the starch in the corn silage stored for 120 days, without causing direct effects on the intake and performance of the animals.